CLOUD SUSTAINABILITY AND FINOPS: BALANCING ENVIRONMENTAL IMPACT AND COST EFFICIENCY - Sardar Mohammed (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
With an emphasis on striking a balance between cost-effectiveness and environmental impact, cloud sustainability and financial operations, or FinOps, have become essential elements of contemporary cloud computing strategy. Through an examination of data center operations transformation, the adoption of sustainable practices, and the integration of FinOps frameworks, this thorough article investigates the intersection of environmental responsibility and cost optimization in cloud computing. Workload optimization, geographic distribution, temporal scheduling, and the application of organizational and technical methods are only a few of the topics that are examined in this article. The article shows how companies may use strategic cloud management, cutting-edge technologies, and integrated frameworks to achieve both operational efficiency and environmental sustainability by analyzing current practices and upcoming trends.